2005
DOI: 10.1038/sj.ijo.0802913
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin levels before and after reduction of overweight due to a low-fat high-carbohydrate diet in obese children and adolescents

Abstract: BACKGROUND: There are conflicting results for ghrelin changes in reduction of overweight. Increasing ghrelin levels in weight reduction are considered to be responsible for compensatory mechanisms that make the reduction of overweight unlikely to be sustained. METHODS:We have analyzed fasting serum ghrelin levels, weighed dietary record and, as biochemical markers of clinically relevant reduction of overweight, leptin, adiponectin and insulin levels and insulin resistance measured by homeostasis model assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 49 publications
5
51
2
3
Order By: Relevance
“…Current study showed that the plasma adiponectin increases following 8 weeks of aerobic training. The changes in the level of adiponectin because of adaptation with the aerobic exercises in most of the previous studies have shown the same results as of this study 30,31,32,32,33,34 . In a study on young and middle-aged women, doing ten weeks of aerobic training resulted in an increase in the plasma levels of adiponectin alongside with a decrease in insulin resistance 30 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Current study showed that the plasma adiponectin increases following 8 weeks of aerobic training. The changes in the level of adiponectin because of adaptation with the aerobic exercises in most of the previous studies have shown the same results as of this study 30,31,32,32,33,34 . In a study on young and middle-aged women, doing ten weeks of aerobic training resulted in an increase in the plasma levels of adiponectin alongside with a decrease in insulin resistance 30 .…”
Section: Discussionsupporting
confidence: 79%
“…While Esposito and colleagues who reported that weight loss in obese women resulted in significant decreases in previously elevated IL-6, IL-8 in addition to a significant increase in the anti-inflammatory adipokine and adiponectin 33 . Also, Reinher etal, proved that weight loss was accompanied by a 15% increase in adiponectin and 19% reduction in leptin 34 . In another study, nine overweight children performed a progressive aerobic program for 8 weeks.…”
mentioning
confidence: 99%
“…This amount of weight loss led to a significant improvement of insulin resistance, cardiovascular risk factors, adiponectin, and leptin levels as demonstrated in our previous studies. [29][30][31][32] Therefore, a too small degree of weight loss seems unlikely as an explanation for the missing effect of weight loss on resistin concentrations. Since resistin is expressed at higher levels in intraabdominal than subcutaneous fat, 12,27 body fat distribution may play an important role in human resistin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Serum immunoreactive ghrelin levels were measu red in duplicate using a commercial radio immunoassay (RIA) that uses 125 I-labeled bioactive ghrelin as a tracer and a rabbit polyclonal antibody raised against full-length octanoylated human ghrelin (Phoenix, Europe, Karlsruhe, Germany), as described previously (25,31). The assay detects both octanoylghrelin and des-octanoyl-ghrelin.…”
Section: Hormone Assay Of Serum Ghrelinmentioning
confidence: 99%